2013
DOI: 10.1002/cctc.201300697
|View full text |Cite
|
Sign up to set email alerts
|

Niobium: Activator and Stabilizer for a Copper‐Based Deacon Catalyst

Abstract: A highly active Cu‐based Deacon catalyst with an enhanced lifetime was developed by combining two corrosion‐resistant high‐throughput reactor setups in this combinatorial study. Catalyst activities were studied in a sequential 10‐fold reactor equipped with online MS. For accelerated catalyst ageing studies, a parallel 10‐fold reactor was used. The starting point was a CuTi mixed‐metal oxide found in former discovery investigations. As development criteria, catalyst stability and HCl conversion were selected. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…The Cu 10 Ti 90 O x catalyst is stable in the first 24 h and the decrease of the conversion is below the measurement error. The performance of this catalyst has been studied in long‐term measurements over 100 h and the results were published recently 45. These studies confirm the usefulness of tenfold reactor systems for reaction performance study over time as well as for ageing studies 44, 45.…”
Section: Resultssupporting
confidence: 53%
“…The Cu 10 Ti 90 O x catalyst is stable in the first 24 h and the decrease of the conversion is below the measurement error. The performance of this catalyst has been studied in long‐term measurements over 100 h and the results were published recently 45. These studies confirm the usefulness of tenfold reactor systems for reaction performance study over time as well as for ageing studies 44, 45.…”
Section: Resultssupporting
confidence: 53%
“…(13) The specific heat capacity, viscosity, density of molten salt, and heat-transfer coefficient of molten salt λ m (kJ·m −1 ·s −1 ·K −1 ) in eq 13 are referenced from the literature. 28,29 The heat capacity of the mixed gas at constant pressure C p (kJ·kmol −1 ·K −1 ) in eq 9 is calculated by eq 14.…”
Section: Resultsmentioning
confidence: 99%
“…17−19 However, catalyst loss caused by particle attrition and low production capacity due to back-mixing of the substances in the fluidized bed lead to increased complexity and cost. 13 Compared to the fluidized-bed reactor, fixed-bed reactors can achieve a higher conversion per pass and reduce operational costs. However, it is difficult to cope with the large amount of reaction heat generated in a fixed-bed reactor.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers generally studied this problem from two perspectives: (1) improvement of catalyst stability and activity and (2) optimization of reactor and reaction conditions. For the first perspective, catalysts generally used in HCl catalytic oxidation, including Cu-, Cr-, Ru-, and Ce-based composite catalysts, were studied to increase the stability and decrease the activity temperature. Sun et al studied the CuKSm x compound catalyst, and their results showed that addition of SmCl 3 promoted dispersion of copper species and provided more active sites of copper species, which increased the catalytic activity of the CuKSm x catalyst. Feng et al studied Cu–K–La/γ-Al 2 O 3 catalysts, and their results showed that Cu, K, and La species highly dispersed on the surface of γ-Al 2 O 3 and addition of KCl provided more active sites of Cu 2+ species and improved the catalytic activity and stability.…”
Section: Introductionmentioning
confidence: 99%